Pharmacokinetic Evaluation of Visnagin and Ammi visnaga Aqueous Extract after Oral Administration in Rats - Haug, Karin G.; Weber, Benjamin; Hochhaus, Guenther; Butterweck, Veronika (Planta Medica, 2012)
The furanochromone visnagin is one of the main compounds of Ammi visnaga L. (syn. Khella) with potential effects on kidney stone prevention. After determination of the pharmacokinetic properties of visnagin after intravenous bolus administration in rats, the aim of the present study was to evaluate the pharmacokinetic properties of visnagin and an aqueous Ammi visnaga extract after oral administration in rats. In two separate experiments, three doses of visnagin (2.5, 5, and 10 mg/kg) solubilized in 25 % Captisol® and three doses of Ammi visnaga extract (standardized on visnagin and containing equivalent amounts of visnagin) were administered by oral gavage to male Sprague-Dawley rats, respectively. Plasma samples were extracted and subsequently analyzed using a validated LC-MS/MS method. Plasma concentration-time profiles were explored by non-compartmental analysis. Visnagin plasma exposure (median AUClast and AUCinf) was significantly increased for all three doses (more than 10-fold for the low dose) when administered as an extract compared to the pure agent. For both the Ammi visnaga extract and the pure compound, AUClast and AUCinf increased disproportionately with an increase in dose. Visnagin resided significantly longer in the body when given in the form of AVE with up to a three times longer median MRTlast and MRTinf for the low dose. Cmax values after AVE administration were elevated and occurred at later time points in comparison to equivalent doses of pure visnagin. The terminal half-life increased with the dose for both AVE and pure visnagin, reaching a maximum value of 1.94 h for the 10 mg/kg pure compound group.In conclusion, the exposure of visnagin is enhanced after extract administration and could result in a superior efficacy of AVE compared to an equivalent dose of visnagin.
Keywords: Ammi visnaga; Apiaceae; visnagin; synergy; nonlinear pharmacokinetics; kidney stones